Hubungan antara dukungan sosial dengan resiliensi yang dimoderatori oleh locus of control pada mahasiswa bidikmisi - Alaiya Choiril Mufidah (PSIKODIMENSIA, 2017)
This study aims to find a positive relationship between social support and resilience of bidikmisi students, to know the positive relationship between locus of control and resilience, and to know the positive relationship between social support and resilience with Locus of Control as moderator variable.This research uses quantitative method with multiple regression analysis technique, Connor & Davidson's scale of adaptation resiliency (CD-RISC), Levinson's scale of Locus of Control adaptation (MLCS), and Social Support scale adapted from Diana Kamilin's thesis. This research examines the relationship between variables X and Y with LOC as mediator. The subjects of this research are students of bidikmisi in UIN Malang as many as 80 subjects. The result of analysis shows that there is a positive relationship between social support and resilience with locus of control as moderator with significance value of 0.431 (p